2016
DOI: 10.1364/josab.33.0000e1
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing the hyperpolarizability of 1D potentials with multiple electrons

Abstract: We optimize the first and second intrinsic hyperpolarizabilities for a 1D piecewise linear potential dressed with Dirac delta functions for N non-interacting electrons. The optimized values fall rapidly for N > 1, but approach constant values of βint = 0.40, γ + int = 0.16 and γ − int = −0.061 above N 8. These apparent bounds are achieved with only 2 parameters with more general potentials achieving no better value. In contrast to previous studies, analysis of the hessian matrices of βint and γint taken with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(43 reference statements)
1
3
0
Order By: Relevance
“…A multi-electron version of the quantum graph model was developed to confirm that graphs with N electrons could still achieve a sizable fraction of the Hamiltonian limits [84]. The limits were similar to those recently reported by Burke et al [88]. In each model, the electrons TABLE II.…”
Section: Quantum Graph Modelssupporting
confidence: 64%
See 1 more Smart Citation
“…A multi-electron version of the quantum graph model was developed to confirm that graphs with N electrons could still achieve a sizable fraction of the Hamiltonian limits [84]. The limits were similar to those recently reported by Burke et al [88]. In each model, the electrons TABLE II.…”
Section: Quantum Graph Modelssupporting
confidence: 64%
“…Recently, the piecewise potential optimization approach was applied to maximize the hyperpolarizability in one dimension of a multiple electron system [88]. The potential models included a δ potential, a sort of triangular potential, and the piecewise potential used in the authors' earlier studies [86,87].…”
Section: Theoretical Explorations Of the Limitsmentioning
confidence: 99%
“…A study on the optimal many-electron nonlinear response can be found in [44]. There is no reason to doubt that the excited state response can be enhanced in the excited state over the ground state configuration for particular systems given that the calculations of the excited state limits as quantified by Equation 28 applies to the manyelectron case and works even when there are interactions between the electrons.…”
Section: E Comparison To Multi-electron Systemsmentioning
confidence: 99%
“…Here we consider multiple noninteracting electrons in an analysis similar to that of Burke and Atherton. [44] The fact that pre-excitation can enhance the intrinsic polarizability has interesting consequences on such multielectron systems. To illustrate, consider a single-particle energy spectrum associated with an external potential.…”
Section: E Comparison To Multi-electron Systemsmentioning
confidence: 99%